Optimalisasi Batu Belah Sebagai Model Tanggul Dalam Upaya Mitigasi Banjir ROB Di Pesisir Pantai - Siti, Rohamayani; Yulianto, Agus; Astuti, Budi (Jurnal Teori dan Aplikasi Fisika, 2024)
Split stone is a type of irregular stone formed from sedimentary rock deposits and sandstone due to weathering and the influence of abrasion in rivers, so split stones are formed. The utilization of split stone as an embankment can be optimized by varying the angle of inclination of the embankment itself. Coastal dikes were built to mitigate tidal floods that occur in coastal areas and cause physical, material, economic and natural losses. Rob flood is a natural disaster characterized by the release of sea water to land. Rob flooding is caused by land subsidence, tidal waves and the absence of wave barriers. From the results of this research, it was found that the dike with the smallest angle is the most optimal embankment if used on the coast, because the more surface area of the embankment that breaks the waves, the less likely the sea waves overflow into land. Keywords: embankment, split stone, rob flood, coastal.